Site nurse-initiated adherence and symptom support telephone calls for HIV-positive individuals starting antiretroviral therapy, ACTG 5031: substudy of ACTG 384. - Robbins, Gregory K; Testa, Marcia A; Su, Max; Safren, Steven A; Morse, Gene; Lammert, Sara; Shafer, Robert W; Reynolds, Nancy R; Chesney, Margaret A (HIV clinical trials, 2013)
Effective and easy to implement interventions to improve adherence to antiretroviral therapy are needed.
Keywords: Adult; Anti-HIV Agents; Female; HIV Infections; Humans; Male; Nurses; Patient Compliance; Telephone